2017
DOI: 10.1002/anie.201702543
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Sustainable Synthesis of Pyrroles from Alcohols and Amino Alcohols

Abstract: The development of reactions that convert alcohols into important chemical compounds saves our fossil carbon resources as alcohols can be obtained from indigestible biomass such as lignocellulose. The conservation of our rare noble metals is of similar importance, and their replacement by abundantly available transition metals, such as Mn, Fe, or Co (base or nonprecious metals), in key technologies such as catalysis is a promising option. Herein, we report on the first base-metal-catalyzed synthesis of pyrrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(92 citation statements)
references
References 58 publications
2
90
0
Order By: Relevance
“…Furthermore,K empe and co-workers demonstrated that precatalyst Mn-18 mediates the synthesis of pyrroles starting from alcohols and amino alcohols (Scheme 21). [120] Diverse functional groups are tolerated in conjunction with low catalyst loadings of 0.5 mol % Mn-18.R elated Co and Fe catalysts are inactive in this reaction. [120] This reaction requires the use of stoichiometric amounts of base.I tc ould be shown that the base is required for the efficient dehydrogenation of the alcohols and for quenching the liberated water.…”
Section: Synthesis Of N-heteroaromaticsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore,K empe and co-workers demonstrated that precatalyst Mn-18 mediates the synthesis of pyrroles starting from alcohols and amino alcohols (Scheme 21). [120] Diverse functional groups are tolerated in conjunction with low catalyst loadings of 0.5 mol % Mn-18.R elated Co and Fe catalysts are inactive in this reaction. [120] This reaction requires the use of stoichiometric amounts of base.I tc ould be shown that the base is required for the efficient dehydrogenation of the alcohols and for quenching the liberated water.…”
Section: Synthesis Of N-heteroaromaticsmentioning
confidence: 90%
“…[120] Diverse functional groups are tolerated in conjunction with low catalyst loadings of 0.5 mol % Mn-18.R elated Co and Fe catalysts are inactive in this reaction. [120] This reaction requires the use of stoichiometric amounts of base.I tc ould be shown that the base is required for the efficient dehydrogenation of the alcohols and for quenching the liberated water. [120] Besides the synthesis of heteroarenes,t heir modification involving aM nc atalyst is also reported.…”
Section: Synthesis Of N-heteroaromaticsmentioning
confidence: 90%
“…In 2017, Kempe and co‐workers successfully synthesized pyrroles 33 by acceptorless‐dehydrogenations followed by condensation of alcohols 32 and amino alcohols 25 using Mn‐3 as the catalyst (Scheme ) …”
Section: C−c/c−x/x−x Multiple Bond Formationsmentioning
confidence: 99%
“…In 2017, Kempe and co-workers successfully synthesized pyrroles 33 by acceptorless-dehydrogenations followed by condensation of alcohols 32 and amino alcohols 25 using Mn-3 as the catalyst (Scheme 24). [44] Recently, Rueping and co-workers had reported a solventfree methodology for the synthesis of pyrroles 33 from 1,4-diols 34 and primary amines 2 in the presence of the complex Mn-29 (Scheme 25). [45] Later, a multi-component synthesis of highly substituted pyrroles 33 via the ADC of 1,2-diols 28, ketones 20, and primary amines 2 in the presence of lutidine derived pincer complex Mn-30, and a catalytic amount of KO t Bu was developed (Scheme 26).…”
Section: Synthesis Of Pyrrolesmentioning
confidence: 99%
“…[4] In contrast, manganese complexes have mainly been employed in oxidation catalysis with reductive transformations remaining scarce. [5] Nevertheless,t he excellent aptitude of manganese in this field has only just been demonstrated in seminal contributions by the groups of Tr ovitch, [6] Zhang, [7] Beller, [8] Kempe, [9] Kirchner, [10] Milstein, [11] and others (Scheme 1). [12] Very recently,t he groups of Kirchner and Clarke reported the first examples of the exploitation of chirality for manganese-catalyzed enantioselective reductive transformations.…”
mentioning
confidence: 99%